2018
DOI: 10.1134/s0001437018060061
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Techniques for Estimation of Physiological State of Blue-Green Algae after Weak External Action

Abstract: Nowadays cyanobacterial blooms in open reservoirs and estuaries became one of the most important ecological problem. The optimal way to solve this problem is to develop innovative methods for controlling the number of bloom-forming cyanobacteria based on weak external actions, which have no serious consequences for the entire ecological system. A novel efficient technique for in vivo estimation of cyanobacterial viability for online ecological monitoring of the results of weak external actions was elaborated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Historically, since the 1960s, researches had noted that changes in physiological state of cyanobacterial cell, occurring when it is grew old or is treated with different external actions, manifest themselves as corresponding changes in the intrinsic selffluorescence spectrum [43]. Several studies have shown that changes in the pigment fluorescence are associated with the changes in the enzymatic activity of the cell and an increase in the permeability of the cell membrane, which can be used as an indicator of aging for cyanobacterial species [41,44]. Today, there is no doubt that the in vivo analysis of fluorescence characteristics of photosynthetic apparatus is a powerful tool for studying the impact of a wide variety of environmental factors on cyanobacteria [24,45].…”
Section: Fluorescence Methods To Study Cyanobacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, since the 1960s, researches had noted that changes in physiological state of cyanobacterial cell, occurring when it is grew old or is treated with different external actions, manifest themselves as corresponding changes in the intrinsic selffluorescence spectrum [43]. Several studies have shown that changes in the pigment fluorescence are associated with the changes in the enzymatic activity of the cell and an increase in the permeability of the cell membrane, which can be used as an indicator of aging for cyanobacterial species [41,44]. Today, there is no doubt that the in vivo analysis of fluorescence characteristics of photosynthetic apparatus is a powerful tool for studying the impact of a wide variety of environmental factors on cyanobacteria [24,45].…”
Section: Fluorescence Methods To Study Cyanobacteriamentioning
confidence: 99%
“…The former gives underestimated results, and the latter, overestimated results. Thus, the analysis of the viability of living cyanobacterial cells should be carried out considering a set of fluorescence spectra with different excitation wavelength, to elucidate the impact of each photosynthetic pigment [41,44,49]. The examples of one-excitation-wavelength studies are also present in the literature [59,60].…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence methods for monitoring physiological state and biological diversity of cyanobacterial cultures are well-known and widely used [13][14][15]. In this work we try to emphasize methods of fluorescence spectroscopy most perspective for industrial and biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%